Splitting failure and deformation evolution of the red argillaceous siltstone disc in the high humidity environment - Zhao, Zenghui; Dong, Zhongtai; Gao, Xiaojie; Liu, Hao (Frontiers in Materials, 2023)
Aiming at the tensile failure of weakly cemented soft rock in high humidity environment, five kinds of red argillaceous siltstone disc samples with different water contents were obtained through maintenance in constant temperature and humidity oven. The Brazilian disc splitting test was carried out to reveal the variation characteristics of splitting mechanical behavior of rock samples in high humidity environment and the influence of water content on the macroscopic strength parameters and splitting deformation. Combined with the SEM (Scanning Eectron Microscope) investigation, the evolution characteristics of microstructure of rock samples with different water content were obtained. Results show that he macroscopic mechanical parameters such as tensile strength and elastic modulus of weakly cemented red sandstone samples under water environment are negatively parabolic correlated with the increase of water content. The moisture content has an important influence on the disc splitting failure mode, forming the main fracture along the radial direction of loading, and showing a local crushing area in the loading area, and the crushing area increases with the increase of water content. Microstructural variation of red sandstone under a high humidity environment is the main reason for its deterioration of macroscopic mechanical properties.